KINERJA ORGANISASI DALAM PELAYANAN PROGRAM IDENTITAS KEPENDUDUKAN DIGITAL (IKD) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMEDANG - Rosnia Nur Hapit (JRPA - Journal of Regional Public Administration, 2025)
This study aims to determine the Organizational Performance in the Digital Population Identity Program (IKD) Service at the Population and Civil Registration Office of Sumedang Regency. The research method used in this study is a qualitative research method. The technique for determining research informants is purposive sampling. With research informants, namely 4 employees of the Population and Civil Registration Office of Sumedang Regency. The data collection techniques used are literature studies and field studies consisting of observation, interviews, documentation and triangulation. The data validity techniques used are credibility, transferability, dependability and confirmability tests. While the data processing procedures in this study are data reduction, data display and conclusion drawing/verification. Based on the results of the study, it was concluded that the Organizational Performance in the Digital Population Identity Program (IKD) Service at the Population and Civil Registration Office of Sumedang Regency has not been implemented properly. The Organizational Performance in the Service of the program has weaknesses in the implementation of its socialization which is based on the lack of community participation in the program. Lack of infrastructure and limited human resources are obstacles to this program. Efforts to overcome these obstacles by optimizing existing resources and submitting the resources needed in the service to the authorities.